Effect of Seed Bio-priming with Microbial Inoculants on Plant Growth, Yield and Yield Contributing Characters in Soybean [Glycine max (L.) Merril] - Pramod Sharma; Arun Bhatt; Bhim Jyoti (International Journal of Economic Plants)
The present investigation was carried out to study the effect of seed bio-priming with microbial inoculants on plant growth, yield and yield contributing characters in soybean [Glycine max (L.) Merril] at Research Station, Gaja and Department of Seed Science and Technology, College of Forestry, Ranichauri, Tehri Garhwal, Uttarakhand, India during kharif season 2014. All the factors in experiment as well as their interactions showed significant influence on plant growth, yield and yield contributing characters in soybean. Among all the treatments, highest field emergence (88.47%) and minimum days to 50% flowering (40.75 days) was recorded in Psf-173 while maximum plant height (30.34 cm) was measured in Th-14. However, seed yield and other contributing characters were improved by PSB bio-primed seed. Among different varieties, Shilajeet variety showed greater value in field emergence (89.27%), plant height (34.25 cm), number of branches plant-1 (4.46), number of pods plant-1 (31.18), pod length (3.39 cm), number of seeds pod-1 (2.71), number of nodule plant-1 (30.68) and seed yield plant-1 (17.03 g). However, earliest days to 50% flowering (39.13 days) was recorded in PS 1092 variety. On the basis of field experiment, PSB proved to be the best bio-agent for enhancing the growth than other tested bio-agents and in respect of selected varieties for priming purpose, Shilajeet was found most promising. The interaction between PSB and Shilajeet also had good combination for above mentioned characters. The present study thus reveals that seed bio-priming enhances growth and yield parameters in soybean. It is therefore suggested that before sowing, soybean seed should be treated with PSB and Psf-173 bio-agents.